2010
DOI: 10.1080/13642537.2010.530085
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic attitudes and practice patterns among psychotherapy trainees in Germany

Abstract: Aim: This study aims to explore if and how values and attitudes from trainees of different psychotherapeutic schools vary during training. Another aim has been to evaluate the extent of their therapeutic selfconfidence during training. Methods: In a cross-sectional study, 171 trainees in German institutes with different theoretical orientations (Psychoanalysis -PA, Psychodynamic Therapy -PT and Cognitive Behavioral Therapy -CBT) participated. Results are reported for two questionnaires: Therapeutic-Attitudes-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 36 publications
6
38
0
5
Order By: Relevance
“…that corresponds to their ideals and wishes. This is in agreement with the conclusion of the German cross-sectional study by Taubner et al (2010), demonstrating students' high identification with attitudes belonging to their theoretical orientation. Moreover, admission to the training was not only a matter of self-selection since the institute chooses students who are found suitable and in accordance with its ideals and norms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…that corresponds to their ideals and wishes. This is in agreement with the conclusion of the German cross-sectional study by Taubner et al (2010), demonstrating students' high identification with attitudes belonging to their theoretical orientation. Moreover, admission to the training was not only a matter of self-selection since the institute chooses students who are found suitable and in accordance with its ideals and norms.…”
Section: Discussionsupporting
confidence: 92%
“…A recent German study approached this issue with the TASC-2 scales (Taubner, Ka¨chele, Visbeck, Rapp, & Sandell, 2010), exploring how values and attitudes in trainees from institutes with different theoretical orientations (psychoanalytic, psychodynamic, and CBT), vary between stages of training. This study is the first showing findings from applying the TASC-2 scales to psychotherapy trainees.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, newer studies confirmed the relationship between a theoretical orientation of a counselor or therapist, on the one hand, and the personality characteristics or philosophical worldview of a counselor or therapist (Poznanski & McLennan, 2003;Tremblay, Herron, & Schultz, 1986) or a trainee (Boswell, Castonguay, & Pincus, 2009;Buckman & Barker, 2010;Taubner, Kächele, Visbeck, Rapp, & Sandell, 2010;Varlami & Bayne, 2007) on the other.…”
Section: Choice and Development Of Theoretical Orientationmentioning
confidence: 81%
“…Their study did not answer the question of whether it was the therapist's personality giving preference to certain variables or whether it was the training which influenced the therapist's priorities. According to Taubner et al (2010), however, therapists' attitudes remain stable during training and their theoretical orientation seems to be rather predetermined. On the other hand, Vasco and Dryden (1994) assume that an experience of dissonance between therapists' personal beliefs and the theoretical and metatheoretical assertions of the chosen theoretical orientation may arise due to their personal or professional development and may lead to a change in theoretical orientation.…”
Section: Choice and Development Of Theoretical Orientationmentioning
confidence: 92%
“…An einer Stichprobe von 171 deutschen Ausbildungsteilnehmerinnen konnten Taubner et al (2010) zeigen, dass schulenkonforme therapeutische Haltungen mit einer höheren Selbstwirksamkeitserwartung der Ausbildungsteilnehmerinnen einhergehen. Das Erleben des eigenen therapeutischen Handelns kann über die Work-InvolveEngagement der Forscherinnen voraus.…”
Section: Behandlungspraxisunclassified